2016
DOI: 10.1016/j.ijpara.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale comparison of expanded gene families in Plasmodium ovale wallikeri and Plasmodium ovale curtisi with Plasmodium malariae and with other Plasmodium species

Abstract: Malaria in humans is caused by six species of Plasmodium parasites, of which the nuclear genome sequences for the two Plasmodium ovale spp., P. ovale curtisi and P. ovale wallikeri, and Plasmodium malariae have not yet been analyzed. Here we present an analysis of the nuclear genome sequences of these three parasites, and describe gene family expansions therein. Plasmodium ovale curtisi and P. ovale wallikeri are genetically distinct but morphologically indistinguishable and have sympatric ranges through the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 83 publications
5
95
3
2
Order By: Relevance
“…into two distinct subspecies: P. ovale curtisi ( Poc , the classic type) and P. ovale wallikeri ( Pow , the variant type) [12]. The nuclear genome sequences further confirmed that Poc and Pow are genetically distinct but morphologically indistinguishable [13]. Further refinements and applications of the molecular methods have enabled enhanced detection of these parasites in molecular surveillance in endemic countries (e.g., [1417]) as well as imported cases [18].…”
Section: Introductionmentioning
confidence: 99%
“…into two distinct subspecies: P. ovale curtisi ( Poc , the classic type) and P. ovale wallikeri ( Pow , the variant type) [12]. The nuclear genome sequences further confirmed that Poc and Pow are genetically distinct but morphologically indistinguishable [13]. Further refinements and applications of the molecular methods have enabled enhanced detection of these parasites in molecular surveillance in endemic countries (e.g., [1417]) as well as imported cases [18].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the variant surface antigens (VSAs), surfin/pvstp gene family possesses 10 members in P. falciparum and two members in P. vivax ; some were also detected in the genomes of Plasmodium ovale curtisi and Plasmodium ovale wallikeri [14, 16, 38, 39]. Furthermore, previous hierarchical clustering analysis identified two surfin/pvstp genes in Plasmodium gallinaceum ( PgSurf1 and PgSurf2 ), indicating that SURFINs are also conserved outside the human malaria parasites [40].…”
Section: Discussionmentioning
confidence: 99%
“…Data compiled from Ansari et al (2016) and Rutledge et al (2017). * indicates one or more assemblies generated from culture-adapted or chimpanzee/monkey-adapted strains. …”
Section: Tablementioning
confidence: 99%
“…But multigene families tend to cluster in the repetitive, difficult-to-assemble subtelomeric regions of chromosomes, making it hard to tally gene numbers accurately. Rutledge et al (2017)’s use of long reads using the Pacific Biosciences next-generation sequencing platform, in combination with extensive manual curation, allows them to overcome that common obstacle and upgrade earlier analyses that were based on much lower-quality assemblies (Ansari et al, 2016). They quantitate large differences between P. ovale and P. malariae in gene complements of the pir , STP1 , and surfin families of surface/exported proteins and, most notably, discover two large, previously undistinguished gene families in P. malariae that they relate to a known P. falciparum RBC invasion protein using 3D protein modeling.…”
mentioning
confidence: 99%